Standardized Phase Angle for Predicting Nutritional Status of Hemodialysis Patients in the Early Period After Deceased Donor Kidney Transplantation - Sukackiene, Diana; Rimsevicius, Laurynas; Miglinas, Marius (Frontiers in Nutrition, 2022)
Background This study was designed to verify whether early posttransplant standardized phase angle (SPhA) determines nutrition status of hemodialysis patients in regard to different nutritional markers and predicts handgrip strength (HGS) 6 months after kidney transplantation. Methods A total of 82 kidney transplant recipients on maintenance hemodialysis treatment entered the study. Nutritional status was evaluated before kidney transplantation, at the hospital discharge date, and 6 months after. We used bioelectrical impedance analysis (BIA), three different malnutrition screening tools, HGS, and anthropometric measurements. Demographic profiles and biochemical nutritional markers were collected. SPhA values, adjusted for age and BMI, were used in our study. Results In the early posttransplant period, kidney transplant recipients lost muscle mass, gained fat mass, and developed mostly negative SPhA, accompanied by significantly lower albumin levels. The subjects with lower than median (<-1.46) SPhAdis [the SPhA (at discharge) adjusted for hospitalization time and the baseline SPhA] displayed lower values of albumin concentration (43.4 vs. 45.1 g/l, p = 0.010), hemoglobin (124 vs. 133 g/l, p = 0.016), GNRI (113 vs. 118, p = 0.041), and HGS (30 vs. 33 kg, p = 0.043). These patients had higher ferritin concentrations (420 vs. 258 mkmol/l, p = 0.026), longer inpatient stays (32 vs. 21 days, p < 0.001), and higher MIS scores (3 vs. 1, p = 0.001). Conclusion At the moment of hospital discharge, lower than the median SPhA is related to protein-energy wasting, represented as lower concentrations of nutrition biomarkers and an active inflammatory response. Higher SPhA before kidney transplantation predicts HGS 6 months after kidney transplantation, especially in women.